Towards a Supernatural Propaganda: The DPRK Myth in the Movie The Big-Game Hunter = World - Husarski, Roman (Studia religiologica, 2020)
For a long time, the world thought that the collapse of the USSR in 1991 would lead to a similar outcome in North Korea. Although the Kim regime suffered harsh economic troubles, it was able to distance itself from communism without facing an ideological crisis and losing mass support. The same core political myths are still in use today. However, after the DPRK left the ideas of socialist realism behind, it has become clearer that the ideology of the country is a political religion. Now, its propaganda is using more supernatural elements than ever before. A good example is the movie The Big-Game Hunter (Maengsu sanyangkkun) in which the Japanese are trying to desacralize Paektu Mountain, but instead experience the fury of the holy mountain in the form of thunderbolts. The movie was produced in 2011 by P’yo Kwang, one of the most successful North Korean directors. It was filmed in the same year Kim Chŏng-ŭn came to power. The aim of the paper is to show the evolution of the DPRK political myth in North Korean cinema, in which The Big-Game Hunter seems to be another step in the process of mythologization. It is crucial to understand how the propaganda works, as it is still largely the cinema that shapes the attitudes and imagination of the people of the DPRK.